THE DETECTION OF ZONES OF ECOLOGICALLY DANGEROUS PROCESSES IN AREAS OF WATER USING THE NATURAL ELECTRICAL FIELD - Kalinin A.V.; Kalinin V.V.; Kulnitskiy L.M.; Vladov M.L.; Shalayeva N.V. (My University, 1996)
The paper deals with the use of the results of geophysical observations in areas of water to solve geological engineering, hydrogeological and geoecological problems. The measurement of natural electrical fields can be used independently as an indicator of rapidly-occurring processes or to assess situations arising as a result of man's intervention in the natural environment. It is particularly useful in areas of freshwater which are most subjected to anthropogenic stress. Four examples are presented to illustrate the use of the electrical field to detect and investigate adverse geoecological situations in areas of water within large industrial agglomerations.